Eco-physiological response of secondary metabolites of teas: Review of quality attributes of herbal tea - Ramphinwa, Maanea Lonia; Mchau, Godwin Richard Ainamensa; Mashau, Mpho Edward; Madala, Ntakadzeni Edwin; Chimonyo, Vimbayi Grace Petrova; Modi, Thembinkosi Albert; Mabhaudhi, Tafadzwanashe; Thibane, Vuyisile Samuel; Mudau, Fhatuwani Nixwell (Frontiers in Sustainable Food Systems, 2023)
Herbal tea is a rich source of secondary metabolites which are reputed to have medicinal and nutritional efficacy. These secondary metabolites are influenced by the abiotic and biotic stresses that improve the production of herbal teas in terms of biomass production, accumulation and partitioning of assimilates of compounds. In this study, various examples of herbal teas have been shown to respond differently to secondary metabolites affected by environmental factors. Thus, the meta-analysis of this study confirms that different herbal teas' response to environmental factors depends on the type of species, cultivar, and the degree of shade that the plant is exposed. It is also evident that the metabolic processes are also known to optimize the production of secondary metabolites which can thus be achieved by manipulating agronomic practices on herbal teas. The different phenolic compound in herbal teas possesses the antioxidant, antimicrobial, antiatherosclerosis, anti-inflammatory, antimutagenic, antitumor, antidiabetic and antiviral activities that are important in managing chronic diseases associated with lifestyle. It can be precluded that more studies should be conducted to establish interactive responses of biotic and abiotic environmental factors on quality attributes of herbal teas.